Upper body posture in Latin American dancers: a quantitative cross-sectional study comparing different postures - Eileen M. Wanke; Manja Mörl-Kreitschmann; Fabian Holzgreve; David Groneberg; Daniela Ohlendorf (BMC, 2023)
Abstract Background In Latin American dance sport (LD), the shoulder girdle and the torso area are particularly stressed due to the dance style specific requirements. The aim of the study was to define differences in various dance specific upper body postures in Latin American dancers and to show gender-specific differences. Methods Three dimensional back scans were performed in n = 49 dancers (28 f/21 m). Five typical trunk positions in Latin American dance (habitual standing and 4 dance specific positions, P1-P5) were compared with each other. Statistical differences were calculated using the Man-Whitney U test, Friedmann test, Conover-Iman test and a Bonferroni-Holm correction. Results Significant gender differences were found in P2, P3 and P4 (p ≤ 0.01-0.001). In P5, the frontal trunk decline, the axis deviation, the standard deviation of the rotation, the kyphosis angle and the shoulder as well as the pelvic rotation were also significantly different. The comparison of the postures showed significant differences between postures 1-5 (p ≤ 0.01-0.001) in the males, (scapular height, right and left scapular angles and pelvic torsion). Similar results were observed for the female dancers, with only the parameters of frontal trunk decline with the lordosis angle as well as the right and left scapular angles being non-significant. Conclusions This study is an approach to better understand the involved muscular structures in LD. Performing LD changes the static parameters of the upper body statics. Further projects are needed to analyse the field of dance even more thoroughly.